Investing in Women along Agribusiness Value Chains - International Finance Corporation (Washington, DC, 2017)
In the coming years, the agribusiness sector will navigate a rapidly shifting, and, in many ways, an increasingly challenging context. The sector will face increased demand for agricultural products, a decline in the availability of arable land, effects of climate change, a pivot from global to regional value chains, technical advances, and a decline in the traditional labor force. Navigating these complex trends will mean seizing new ways to increase the productivity and efficiency of agribusiness value chains. One promising way to contribute to both goals is to apply gender-smart solutions. This report calls on the private sector to invest in closing gaps between men and women in agribusiness. It focuses on four different stages of a simplified value chain: (1) input provision and use; (2) production; (3) post-harvest processing and storage; and (4) transportation, marketing, and sales. At each value chain stage the report helps companies to identify potential benefits from closing gender gaps by reviewing women’s contributions and constraints within each stage, outlining gender-smart solutions for the private sector, demonstrating the business rationale for making gender-smart investments, and presenting best practice case studies.